Irritable Bowel Syndrome and Neurological Deficiencies: Is There A Relationship? The Possible Relevance of the Oxidative Stress Status - Balmus, Ioana-Miruna (Medicina (Kaunas), 2020)
Background: Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders, exhibiting complex and controversial pathological features. Both oxidative stress and inflammation-related reactive oxygen species production may be involved in IBS pathological development. Thus, we focused on several aspects regarding the causes of oxidative stress occurrence in IBS. Additionally, in the molecular context of oxidative changes, we tried to discuss these possible neurological implications in IBS. Methods: The literature search included the main available databases (e.g., ScienceDirect, Pubmed/Medline, Embase, and Google Scholar). Articles in the English language were taken into consideration. Our screening was conducted based on several words such as “irritable bowel syndrome”, “gut brain axis”, “oxidative stress”, “neuroendocrine”, and combinations. Results: While no consistent evidence suggests clear pathway mechanisms, it seems that the inflammatory response may also be relevant in IBS. The mild implication of oxidative stress in IBS has been described through clinical studies and some animal models, revealing changes in the main markers such as antioxidant status and peroxidation markers. Moreover, it seems that the neurological structures involved in the brain-gut axis may be affected in IBS rather than the local gut tissue and functionality. Due to a gut-brain axis bidirectional communication error, a correlation between neurological impairment, emotional over-responsiveness, mild inflammatory patterns, and oxidative stress can be suggested. Conclusions: Therefore, there is a possible correlation between neurological impairment, emotional over-responsiveness, mild inflammatory patterns, and oxidative stress that are not followed by tissue destruction in IBS patients. Moreover, it is not yet clear whether oxidative stress, inflammation, or neurological impairments are key determinants or in which way these three interact in IBS pathology. However, the conditions in which oxidative imbalances occur may be an interesting research lead in order to find possible explanations for IBS development.